2019
DOI: 10.1007/s11837-019-03761-9
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Rapid Pore Classification in Metal Additive Manufacturing

Abstract: The additive manufacturing of metals requires optimisation to find the melting conditions that give the desired material properties. A key aspect of the optimisation is minimising the porosity that forms during the melting process. A corresponding analysis of pores of different types (e.g. lack of fusion or keyholes) is therefore desirable. Knowing that pores form under different thermal conditions allows greater insight into the optimisation process. In this work, two pore classification methods were trialled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 19 publications
(21 reference statements)
0
40
0
Order By: Relevance
“…There is no clear definition of the correlation between sphericity value and defect type. Yet, Snell et al [ 55 ] recently showed, based on clustered results, that sphericity factors lower than 0.6, higher than 0.7, and higher than 0.92 represent an irregular shape that may be associated with lack of fusion, keyholes (usually, the result of high energy causing localized vaporization), and gas porosity, respectively. Irregular pores may also be attributed to partially melted powder particles resulting from insufficient laser energy [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear definition of the correlation between sphericity value and defect type. Yet, Snell et al [ 55 ] recently showed, based on clustered results, that sphericity factors lower than 0.6, higher than 0.7, and higher than 0.92 represent an irregular shape that may be associated with lack of fusion, keyholes (usually, the result of high energy causing localized vaporization), and gas porosity, respectively. Irregular pores may also be attributed to partially melted powder particles resulting from insufficient laser energy [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to use machine learning for pore classification. Snell et al [15] classified pores using unsupervised machine learning methods, such as K-means clustering. Unsupervised learning is a very interesting approach to classify pores without prior knowledge about the used data set.…”
Section: Pore Types In Alsi10mg Components Using Laser Powder Bed Fusionmentioning
confidence: 99%
“…Fatigue fracture in SLM parts originates from their internal defects. (Rao et al, 2019) (Günther et al, 2017) (Beevers et al, 2018) Therefore, as the mechanical properties of SLM parts are significantly affected by the internal defects present in them, computed tomography (CT) has been used to detect the presence of the defects in SLM parts (Snell et al, 2020) (Sangid et al, 2020) (Wits et al, 2016) (Kasperovich et al, 2016). However, from the viewpoint of strength design, it is necessary to determine the internal defect size and investigate its effect on the fatigue characteristics of SLM parts before production.…”
Section: Introductionmentioning
confidence: 99%